MINIMALLY PROCESS PADA BUAH RAMBUTAN DAN PERUBAHAN KANDUNGAN VITAMIN C SELAMA PENYIMPANAN BEKU - Rozana Rozana; Sunardi Sunardi (Journal of Food Technology and Agroindustry, 2021)
Fresh-cut rambutan products not only have to look fresh, but must have sensory properties (aroma, taste, texture, and visual appeal) similar to fresh products, they must also be safe, healthy and nutritious. So it is necessary to characterize the quality, especially vitamin C from fresh-cut rambutan products which are vacuum packed and stored at frozen temperatures. The purpose of this study was to determine the effect of frozen storage on changes in vitamin C in minimally processed rambutan. The material used in this study was fresh rambutan fruit, Si Kuning variety, obtained from rambutan collectors in Tengguli Village, Sajad District, Sambas Regency. The fruit used is fruit at the ripe stage. The level of vitamin C at the beginning of storage was 14.0772%. The observed peeled rambutan was stored at -15 oC for 20 days, vacuum packed and without vacuum. The results of testing for vitamin C levels were carried out on the 20th day of storage. The level of vitamin C of rambutan after 20 days of storage which was stored at -15 oC decreased drastically when compared to the vitamin C content on day 0. The percentage of loss of vitamin C reached 60% in vacuum packaged rambutan, and the proportion decreased by 70% in non-vacuum packed rambutan.